Slc26a3 deletion alters pH‐microclimate, mucin biosynthesis, microbiome composition and increases the TNFα expression in murine colon. (20th June 2020) - Kini, Archana; Singh, Anurag K.; Riederer, Brigitte; Yang, Ines; Tan, Xinjie; di Stefano, Gabriella; Tan, Qinghai; Xiao, Fang; Xia, Weiliang; Suerbaum, Sebastian; Seidler, Ursula
Abstract: Aim: SLC26A3 (DRA) mediates the absorption of luminal Cl − in exchange for HCO3 − in the distal intestine. Its expression is lost in congenital chloride diarrhoea (CLD) and strongly decreased in the presence of intestinal inflammation. To characterize the consequences of a loss of Slc26a3 beyond disturbed electrolyte transport, colonic mucus synthesis, surface accumulation and composition, pH microclimate, microbiome composition and development of inflammation was studied in slc26a3 −/− mice. Methods: The epithelial surface pH microclimate and the surface mucus accumulation in vivo was assessed by two photon microscopy in exteriorized mid colon of anaesthetized slc26a3 −/− and wt littermates. Mucus synthesis, composition and inflammatory markers were studied by qPCR and immunohistochemistry and microbiome composition by 16S rRNA sequencing. Results: Colonic pH microclimate was significantly more acidic in slc26a3 −/− and to a lesser extent in cftr −/− than in wt mice. Goblet cell thecae per crypt were decreased in slc26a3 −/− and increased in cftr −/− colon. Mucus accumulation in vivo was reduced, but much less so than in cftr −/− colon, which is possibly related to the different colonic fluid balance. Slc26a3 −/− colonic luminal microbiome displayed strong decrease in diversity. These alterations preceded and maybe causally related to increased mucosal TNFα mRNA expression levels and leucocyte infiltration in the mid‐distal colon of slc26a3 −/− but not of cftr −/− mice. Conclusions: These findings may explain the strong increase in the susceptibility of slc26a3 −/− mice to DSS damage, and offer insight into the mechanisms leading to an increased incidence of intestinal inflammation in CLD patients.